Preclinical testing of an oncolytic parvovirus: standard protoparvovirus H-1PV efficiently induces osteosarcoma cell lysis In vitro - Geiss, Carsten; Lacroix, Jeannine (Viruses, 2017)
Osteosarcoma is the most frequent malignant disease of the bone. On the basis of early clinical experience in the 1960s with H-1 protoparvovirus (H-1PV) in osteosarcoma patients, this effective oncolytic virus was selected for systematic preclinical testing on various osteosarcoma cell cultures. A panel of five human osteosarcoma cell lines (CAL 72, H-OS, MG-63, SaOS-2, U-2OS) was tested. Virus oncoselectivity was confirmed by infecting non-malignant human neonatal fibroblasts and osteoblasts used as culture models of non-transformed mesenchymal cells. H-1PV was found to enter osteosarcoma cells and to induce viral DNA replication, transcription of viral genes, and translation to viral proteins. After H-1PV infection, release of infectious viral particles from osteosarcoma cells into the supernatant indicated successful viral assembly and egress. Crystal violet staining revealed progressive cytomorphological changes in all osteosarcoma cell lines. Infection of osteosarcoma cell lines with the standard H-1PV caused an arrest of the cell cycle in the G2 phase, and these lines had a limited capacity for standard H-1PV virus replication. The cytotoxicity of wild-type H-1PV virus towards osteosarcoma cells was compared in vitro with that of two variants, Del H-1PV and DM H-1PV, previously described as fitness variants displaying higher infectivity and spreading in human transformed cell lines of different origins. Surprisingly, wild-type H-1PV displayed the strongest cytostatic and cytotoxic effects in this analysis and thus seems the most promising for the next preclinical validation steps in vivo.